Socialization of the Use of Perplexity AI in Improving the Quality of Research and Student in Indonesia : Penelitian - Mohamad Sudi; Taryana; Rinovian Rais; St. Rahmah; Nabila Cecilia Marasabessy (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The author conducted this socialization towards students and junior lecturers. This socialization was conducted during the author's teaching hours and informal discussions among colleagues in the office. The result in this article show the author conducted lasted for approximately four meetings with students at the author's teaching place with the concept of socializing the use of Perpexity AI once and directly practicing writing journals and thesis frameworks with three evaluations. When conducting socialization, the author explained a number of advantages of Perplexity AI, including: 1. More Optimal Search Engine Capabilities: Google Search is more optimal in searching using keywords. If we enter a long sentence, Google often cannot find search results. This is different from Perplexity AI which is able to understand the context of the writing we input, whether it is in the form of long text or just keywords. Anyone who uses it will certainly be facilitated. 2. More Accurate Answers: Although ChatGPT has a broad understanding of language, they may not always understand the context in depth. This causes answers that are less precise or not in accordance with what the user means. Unlike Perplexity which has a better understanding of context so that its answers can be more relevant and accurate. 3. Chatbot with Advanced Capabilities: This AI can respond to any conversation you make, even if it's just a "hello". The answers are also very friendly so that we can feel comfortable when chatting with this search engine. Even so, his knowledge is so broad that we can ask him anything, from trivial questions to very difficult questions. He will try to answer it as accurately as possible complete with references. 4. Displaying Answer Sources Transparently: Every answer it provides is usually obtained from Google search results. Even so, Perplexity AI is able to summarize it for you. So, you don't need to bother getting the gist of the answer. One thing that makes this AI so helpful is that it will display the source of information for each answer. Not just one source, at least two to five sources of information can be found. 5. Fast and Efficient: No need to wait long to see the answer from Perplexity. After you type the question, the answer will immediately appear below it. Even so, this speed is also influenced by several factors. The more difficult and complex the question you throw, of course the answering process will also be longer. So, this speed issue must be adjusted to these variables. In fact, among the advantages that the author mentioned above, there are still many other advantages possessed by Perplexity AI such as performance evaluation, ease of use, can be used on PC or smartphone, and so on. The advantages possessed by Perplexity AI, researchers are that it can improve the quality of student research, both journals and theses.